The Intervention to Enhace the Coping of Parents of Children with Autism - Nayluzzuharo' N, Fanny; Widyawati, Ika Yuni; Ulfiana, Elida (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2021)
Introduction: Autism is a disruption verbal, nonverbal, and social interaction growth in children. Children with autism spectrum disorder have a different parenting program with normal children. A mother who has autism spectrum disorder children need for more space up her time to treat their children right, and sometimes they will have their stress moments because of what they think about their autism spectrum disorder children. This study aims to explain the interventions to enhace the coping of parents of children with autism.Method: The literature was searched using electronic database: Scopus, CINAHL, Science Direct, Sage, Google Schoolar with inclusion criteria include: parents of children with Autism Spectrum Disorder, articles published in 2011-2021 using experimental studies in English and Indonesian. Ten articles obtained for review.Result: Ten articels that fulfill a searching requirement and chosen to be analyzed. From ten articels there are divided into two interventions on it, Cognitive Based Intervention wich are Parent Education Program, Coping Effectiveness Training, Mindfulness-Based Interventions, Problem-Solving Skills Training, and Psychological Based Intervention wich are Virtual Resilience Intervention.Conclusion: This research shows that some interventions or programs that have been examined effectively can increase coping at parents who has autism spectrum disorder children. The intervention that is considered the most effective and often used is the parent education program.